The Influence of Service Quality, Marketing Strategy and Consumer Trust on Construction Service User Decisions at PT Karya Harmoni Oasis - Hendra Jonathan Sibarani; Serly; Jesly Florencia (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to examine and analyze the effect of service quality, marketing strategies and consumer trust on the decision to use construction services at PT Karya Harmoni Oasis. Decisions on the use of construction services that have decreased due to sub-optimal service quality, unattractive marketing strategies, decreased consumer confidence. The approach in this research is a quantitative approach. In this study, researchers used quantitative descriptive research methods. The sample in this study used all 109 customers and used a sample collection technique, namely saturated sampling. The results of the calculation of the partial hypothesis testing obtained tcount> ttable or 2.203> 1.983 and significant obtained 0.046 <0.05, tcount> ttable or 4.298> 1.983 and significant obtained 0.000 <0.05, tcount> ttable or 3,552> 1,983 and the significant obtained is 0.001 <0.05, it means that partially Service Quality, Marketing Strategy and Consumer Trust have a positive and significant effect on the Decision to Use Construction Services at PT Karya Harmoni Oasis. The test results obtained by the value of F count (21,710)> F table (2.69) and a significance probability of 0.000 <0.05, meaning that simultaneously Service Quality, Marketing Strategy and Consumer Trust have a positive and significant effect on the Decision to Use Construction Services at PT Karya Harmoni Oasis.